Assessment of in-house build low cost solar panel simulator. Issue 1 (May 2021) - Fauzi, F; Tajudin, M F N; Mohamed, M F; Azmi, A; Manaf, N A A
Abstract: It is well known that solar simulator is a very important equipment in solar panels research and development (R&D). Solar simulator is mainly used to assess the efficiency of solar panels. However, the cost to acquire such system is expensive and prone to malfunction when used repeatedly. The cost to repair solar simulator when malfunction is also expensive and time consuming. As an alternative, low cost solar simulator has been built independently by a group of researcher from Faculty of Electrical Engineering Technology (FTKE), University of Malaysia, Perlis (UniMAP) using 88 GU-10 halogen bulbs. This paper presents the assessment of the in-house build low cost solar panel simulator. The simulator was tested in three separate experiments to plot the current-voltage (IV) curve. The IV curves obtained from these experiments were analysed to determine the irradiance input (in Wm −2 ) of the solar simulator. Results have shown that the in-house build solar simulator has an input of 350 ∼ 400 Wm −2 if solar panels are suspended 20 cm above the halogen bulbs.